Development of antiproliferative long-circulating liposomes co-encapsulating doxorubicin and curcumin, through the use of a quality-by-design approach - Tefas, Lucia Ruxandra (Drug Des Devel Ther, 2017)
The aim of this work was to use the quality-by-design (QbD) approach in the development of long-circulating liposomes co-loaded with curcumin (CUR) and doxorubicin (DOX) and to evaluate the cytotoxic potential of these liposomes in vitro using C26 murine colon carcinoma cell line. Based on a risk assessment, six parameters, namely the phospholipid, CUR and DOX concentrations, the phospholipid:cholesterol molar ratio, the temperature during the evaporation and hydration steps and the pH of the phosphate buffer, were identified as potential risk factors for the quality of the final product. The influence of these variables on the critical quality attributes of the co-loaded liposomal CUR and DOX was investigated: particle size, zeta potential, drug loading and entrapment efficiency. For this, a 2(6−2) factorial design was employed to establish a proper regression model and to generate the contour plots for the responses. The obtained data served to establish the design space for which different combinations of variables yielded liposomes with characteristics within predefined specifications. The validation of the model was carried out by preparing two liposomal formulations corresponding to the robust set point from within the design space and one outside the design space and calculating the percentage bias between the predicted and actual experimental results. The in vitro antiproliferative test showed that at higher CUR concentrations, the liposomes co-encapsulating CUR and DOX had a greater cytotoxic effect than DOX-loaded liposomes. Overall, this study showed that QbD is a useful instrument for controlling and optimizing the manufacturing process of liposomes co-loaded with CUR and DOX and that this nanoparticulate system possesses a great potential for use in colon cancer therapy.